In vitro anticolon antibody production by mucosal or peripheral blood lymphocytes from patients with ulcerative colitis. Issue 12 (December 1990) - Hibi, T; Ohara, M; Toda, K; Hara, A; Ogata, H; Iwao, Y; Watanabe, N; Watanabe, M; Hamada, Y; Kobayashi, K
Abstract : Serum anticolon antibody and in vitro anti-colon antibody production by peripheral blood and mucosal lymphocytes was investigated in patients with ulcerative colitis. The frequency of serum anticolon antibody was 71% in 41 patients with ulcerative colitis, estimated by enzyme linked immunosorbent assay (ELISA) using isolated rat colon epithelial cells. This finding confirms our previous report on the frequency of serum anticolon antibody detected by flow cytometry analysis. The estimated frequencies of IgG anticolon antibody secreting cells were 1.5-12.5/10(6) cells in the colonic mucosa and 0.1-0.5/10(6) cells in peripheral blood, from patients with ulcerative colitis when Epstein-Barr virus (EBV) was used as a B cell polyclonal activator. Poisson analysis of limiting dilution culture showed that about one per 140 IgG cells in the colonic mucosa synthesised anticolon antibody. Two monoclonal IgG antibodies were obtained from EBV transformed anticolon antibody secreting cells by limiting dilution method. One reacted with goblet cells in the intestine, and the other reacted mainly with colonic epithelial cells. These results suggest that heterogeneous anticolon antibodies are present in patients with ulcerative colitis and that colonic mucosa may be the main source of anticolon antibody. Local autoimmune reaction might have an important role in causing the inflammation of colonic mucosa in this disease.